2019
DOI: 10.3390/electronics8090996
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of an Electromagnetic Fully Variable Valve Train with a Magnetorheological Buffer

Abstract: Electromagnetic fully variable valve train (EMVT) technology promises to improve the fuel economy and optimize the engine performance. A novel EMVT equipped with a magnetorheological buffer (EMVT with MR buffer) is proposed to suppress the valve seating impact in this paper. The magnetorheological buffer can adjust the damping characteristics of the whole system in the seating process. Valve precise motion control and better seating performance can be achieved through the coordinated control of electromagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The fully variable valve system works as follows 11 : when the valve opens, the current is applied to the EMLA coil generating an axial electromagnetic force to drive the valve. When the valve closes, the MR buffer will be turned on before the valve is seated.…”
Section: System Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The fully variable valve system works as follows 11 : when the valve opens, the current is applied to the EMLA coil generating an axial electromagnetic force to drive the valve. When the valve closes, the MR buffer will be turned on before the valve is seated.…”
Section: System Overviewmentioning
confidence: 99%
“…Simulation and experiment results showed that valve seating characteristics become stable and soft when the engine is at the speed of 5000 r/min. Guo et al 10 and Zhu et al 11 have studied a fully variable valve system that uses the magnetorheological buffer (MR buffer) to realize seat cushioning, which could minimize the seating velocity and rebound height of the valve. In the system, the electromagnetic linear actuator (EMLA) is a moving coil linear motor that the axial driving force is generated by the current-carrying coil in the permanent magnetic field to drive the valve moving.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the buffers used in research and development mainly include aluminum honeycomb buffers, hydraulic buffers, mechanical buffers, magnetorheological fluid buffers, and metal rubber buffers. [22][23][24][25][26][27][28] The aluminum honeycomb buffer is the most used and most mature buffer among the successfully launched landers. The buffer has low mass, good energy absorption effect, stable operation, adjustable buffer stroke, and low dependence on the environment.…”
Section: Introductionmentioning
confidence: 99%